Essential and toxic trace elements and vitamins in human health - Prasad, Ananda S. (Ananda Shiva); Brewer, George J., 1930- (Academic Press, an imprint of Elsevier, 2020)
"Essential and Toxic Trace Elements and Vitamins in Human Health is a comprehensive guide to the wide variety of micronutrients that affect human health, including fat-soluble and water-soluble vitamins that support diverse biochemical functions, trace elements with established and suggested links to health maintenance, and elements with known human toxicity such as arsenic, cadmium, and lead. An essential reference text for nutritionists working in academia and functional food and supplement industries, dieticians, and clinicians, Essential and Toxic Trace Elements and Vitamins in Human Health provides an in-depth look at toxic trace elements and essential vitamins and minerals and their direct influence on the body's overall health with expert research from renowned scientists"--Publisher's description